Bowel obstruction from intramural hematoma in two children treated with low molecular weight heparin: Case report and review of the literature - Richard M. Schroeder; Jonathan E. Kohler; Grace Z. Mak; Jessica J. Kandel (Elsevier, 2014)
Low molecular weight heparin (LMWH) is frequently employed in children to prevent extension of intravascular thrombosis. However, this therapy can result in pathologic bleeding, including spontaneous intramural hematoma of the intestinal wall. In this report, we describe two cases of intestinal obstruction resulting from intramural hematomas during therapeutic LMWH therapy in children. The diagnostic studies and management of spontaneous intramural hematoma in children are discussed.